THE INFLUENCE OF GENDER DIVERSITY, NATIONALITY, AND EDUCATION OF THE BOARD OF DIRECTORS ON CSR IN INDONESIA SHARIA BANKING - Dessy Noor Farida (Univeristas Islam Bandung, 2020)
Public awareness of the damage to the surrounding environment due to the industrial activities of large companies, making the public need information about the extent to which the company is responsible for the damage. To maintain the stability of its business, the company is expected to be able to contribute to the community and its environment by implementing CSR. Diversity of directors within an organization can create new norms and hopes that can be a strong driver for implementing CSR in developing countries. This study aims to examine the effect of diversity on the board of directors on CSR disclosure in Indonesian Sharia banking. This research is quantitative. The sample used was all Islamic Commercial Banks in Indonesia totaling 13 banks. Technical analysis of data using multiple linear regression tests. The results confirm that national diversity affects the disclosure of CSR, but gender diversity and educational diversity are not significant to CSR disclosure. This study has an adjusted R2 of 65.6%.